Deserción escolar de estudiantes en instituciones educativas del nivel secundario de la localidad de Caballococha 2021 - Torres Guerra, Jorge Luis (2023)
The present study corresponds to the descriptive type of research with a quantitative approach; it responds to the non-experimental design of the simple descriptive type. A population of 288 students was considered as the sample, for which non-probabilistic sampling was used. The technique used was the survey and as an instrument the questionnaire, being structured for each variable with its respective dimension and item; likewise, they were validated by three teachers with expertise in the subject and to obtain the reliability the Crombach's alpha statistic was used, which indicates that they are reliable. Statistical graphs were used to analyze the tables of data percentages and averages. The most relevant conclusions were the following: The causes that generate high school dropout in secondary level students of the Educational Institutions of Caballococha during the year 2021 are family dysfunction with 73%, followed by low economic income with 61% and low school performance with 57%. Family dysfunction and low income are the main causes that generate a high dropout rate among secondary school students in the educational institutions of Caballococha during the year 2021.